New Insights into Molecular Mechanisms of Immune Complex-Induced Injury in Lung - Ward, Peter A.; Fattahi, Fatemeh; Bosmann, Markus (Frontiers in Immunology, 2016)
While the phlogistic activities of IgM or IgG immune complexes (IC) have been well established as complement-activating agents and seem likely to play important roles in humans with vasculitis, certain types of glomerulonephritis as well as in a variety of autoimmune diseases, the predominant clinical strategies have involved the use of immunosuppressive or antiinflammatory drugs. Over the past decade, new insights into molecular events developing during IC models in rodents have identified new phlogistic products that may be candidates for therapeutic blockade. Extracellular histones, located in the web-like structures of neutrophil extracellular traps (NETs), are released from complement-activated polymorphonuclear neutrophils (PMNs) downstream of IC deposition. Extracellular histones appear to be a new class of highly tissue-damaging products derived from complement-activated PMNs. Histones have also been discovered in cell-free broncho-alveolar lavage fluids (BALFs) from humans with acute respiratory distress syndrome (ARDS). Recent studies emphasize that, in the setting of ARDS-like reactions in rodents, extracellular histones are released and are exceedingly proinflammatory, tissue damaging and prothrombotic. Such studies suggest that in humans with ARDS, extracellular histones may represent therapeutic targets for blockade.